2020
DOI: 10.1093/toxsci/kfaa079
|View full text |Cite
|
Sign up to set email alerts
|

Manganese-induced Mitochondrial Dysfunction Is Not Detectable at Exposures Below the Acute Cytotoxic Threshold in Neuronal Cell Types

Abstract: Manganese (Mn) is an essential metal, but excessive exposures have been well-documented to culminate in neurotoxicity. Curiously, the precise mechanisms of Mn neurotoxicity are still unknown. One hypothesis suggests that Mn exerts its toxicity by inhibiting mitochondrial function, which then (if exposure levels are high and long enough) leads to cell death. Here, we used a Huntington’s disease cell model with known differential sensitivities to manganese—STHdhQ7/Q7 and STHdhQ111/Q111 cells—to examine the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 81 publications
2
14
1
Order By: Relevance
“…At the same time, in SH-SY5Y cells Mn exposure (0–100 μM Mn for 5 h) resulted in an increase in cellular oxygen consumption rate, SOD2 activity, and H 2 O 2 production without a significant elevation of superoxide production observed over entire physiological to pathological range [ 108 ]. These findings contradict our observations of lack of Mn-induced mitochondrial dysfunction at exposure ranges lower than cytotoxic [ 96 ]. Given this inconsistency one could propose the physiological regulatory role of Mn-induced mitochondrial H 2 O 2 production at nearly physiological exposure ranges.…”
Section: Mn-induced Alterations In Subcellular and Multicellular Biologycontrasting
confidence: 99%
See 1 more Smart Citation
“…At the same time, in SH-SY5Y cells Mn exposure (0–100 μM Mn for 5 h) resulted in an increase in cellular oxygen consumption rate, SOD2 activity, and H 2 O 2 production without a significant elevation of superoxide production observed over entire physiological to pathological range [ 108 ]. These findings contradict our observations of lack of Mn-induced mitochondrial dysfunction at exposure ranges lower than cytotoxic [ 96 ]. Given this inconsistency one could propose the physiological regulatory role of Mn-induced mitochondrial H 2 O 2 production at nearly physiological exposure ranges.…”
Section: Mn-induced Alterations In Subcellular and Multicellular Biologycontrasting
confidence: 99%
“…Generally, the role of complex II as a target for Mn toxicity corroborates our findings on different modes of prooxidant effect of Mn (0–200 µM Mn for 24 h) and rotenone, a specific electron transport chain (ETC) complex I inhibitor, in human-induced pluripotent stem cell-derived postmitotic mesencephalic dopamine neurons [ 95 ]. However, our recent findings demonstrate that mitochondrial dysfunction is observed only at cytotoxic exposure doses (0–300 µM for 24 h), being indicative that there are neurotoxic insults not associated with acute cell death that are independent of mitochondria dysfunction [ 96 ].…”
Section: Mn-induced Alterations In Subcellular and Multicellular Biologymentioning
confidence: 99%
“…Studies have found that Mn deficiency is related to HD [ 111 , 112 , 113 , 114 , 115 , 116 ], and exogenous Mn supplementation can promote the clearance of mutant HTT protein aggregates in striatum cells [ 117 , 118 ]. A recent study reported that Mn-induced mitochondrial dysfunction in HD cells could only be detected at an exposure dose above the acute toxicity threshold [ 119 ]. One study found that Cd exposure increased oxidative stress, caused apoptosis, and altered metal transport in heterozygous HTT striatum cells [ 120 ].…”
Section: Neurological Disorders With Mitochondrial Dysfunction and Oxidative Stressmentioning
confidence: 99%
“…Mn overexposure can cause mitochondrial dysfunction accompanied by the release of cytochrome C and caspase 3/7 activation, resulting in the death of dopaminergic neurons. Notably, Mn-induced mitochondrial dysfunction may occur after acute cytotoxic thresholds have been reached (Warren et al, 2020). Additionally, S-nitrosylation of dynamin-related protein 1 (Drp1) has been found to result in excessive mitochondrial fission and the aggravation of Aβ-induced synaptic damage (Nakamura et al, 2013).…”
Section: Autophagy and Mn-induced Nitrosative Stressmentioning
confidence: 99%